How things are made - "Parker, Steve" (Kingfisher London, 1994)
Focusing on how things are made, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book examines the different ways in which a range of objects of interest to children are made, and the materials, machinery and people involved.